Method for manufacturing dry development toner
A dry-type toner production method using a non-crystalline polyester resin with polyethylene terephthalate in an open-roll mixer achieves both glossy and hot offset properties, addressing the balance issue in existing toners.
Patent Information
- Application Number
- JP2024118616
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2044-07-24
AI Technical Summary
Existing toners struggle to balance glossy and hot offset properties, with liquid developers either failing to address hot offset after drying or not optimizing both properties simultaneously.
A method for producing a dry-type toner using a non-crystalline polyester resin blended with polyethylene terephthalate, mixed using an open-roll two-axis mixer, followed by kneading, crushing, and dividing to achieve a balance between glossy and hot offset properties.
The method results in a toner that excels in both glossy and hot offset properties, maintaining elasticity and resistance to heat without compromising image quality.
Smart Images

Figure 2025017359000001 
Figure 2025017359000002 
Figure 2025017359000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a toner for dry development used in dry development of a latent image formed in an electrophotographic method, an electrostatic recording method, an electrostatic printing method or the like. [Background technology]
[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of toners for developing electrostatic images capable of producing images with high gloss (luster) in order to meet the demands for higher image quality.
[0003] On the other hand, as a polyester resin used as a binder resin for a toner for developing an electrostatic image, a resin using polyethylene terephthalate together with a raw material monomer has been investigated.
[0004] Patent Document 1 discloses a liquid developer containing toner particles containing a binder resin and a colorant, a dispersant, and an insulating liquid, in which the binder resin is a polyester resin that is a polycondensate of raw materials containing an alcohol component, a carboxylic acid component, and polyethylene terephthalate, the acid value of the polyester resin is 15 mgKOH / g or more and 70 mgKOH / g or less, and the amine value of the dispersant is 50 mgKOH / g or more and 300 mgKOH / g or less.
[0005] Patent Document 2 discloses a liquid developer in which toner particles containing a binder resin and a colorant are dispersed in an insulating liquid, wherein the binder resin contains a polyester resin, the insulating liquid contains 50 mass % or more of saturated aliphatic hydrocarbons, the initial boiling point of the insulating liquid is 190°C or more and 240°C or less, and the difference between the initial boiling point and the dry point is 15°C or less, and the liquid developer also discloses that polyethylene terephthalate may be used as part of the alcohol component and carboxylic acid component.
[0006] Patent Document 3 discloses a binder resin composition for toner containing an amorphous resin and a crystalline resin, in which the amorphous resin contains polyester-based resin A which is a polycondensate of an alcohol component containing an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom, a carboxylic acid component, and polyethylene terephthalate, and the crystalline resin contains polyester-based resin C which is a polycondensate of an alcohol component containing 50 mol % or more and 100 mol % or less of ethylene glycol, and a carboxylic acid component, and the mass ratio of the amorphous resin to the crystalline resin (amorphous resin / crystalline resin) is 65 / 35 or more and 95 / 5 or less. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication No. 2021-56477 [Patent Document 2] JP 2020-86376 A [Patent Document 3] JP 2019-66536 A Summary of the Invention [Problem to be solved by the invention]
[0008] Glossiness is in a contradictory relationship with hot offset resistance, which is one of the main fixing performances, and a toner that can achieve both is required, but the liquid developers described in Patent Documents 1 and 2 fix the image by drying the insulating liquid with heat after coating with a bar coater, so there is no problem with hot offset. Furthermore, Patent Document 3 does not consider achieving both glossiness and hot offset resistance, and there is room for improvement.
[0009] The present invention relates to a method for producing a toner for dry development, which is capable of achieving both high gloss and high hot offset resistance. [Means for solving the problem]
[0010] The present invention relates to [1] A method for producing a toner for dry development containing an amorphous polyester resin A, the amorphous polyester resin A being a polycondensate of an alcohol component, a carboxylic acid component, and polyethylene terephthalate, the method comprising: a step of melt-kneading a mixture containing the amorphous polyester resin A using an open-roll type twin-screw kneader; a step of pulverizing and classifying the resulting kneaded product to obtain toner base particles; and a step of mixing the resulting toner base particles with an external additive; and [2] A method for fixing a toner, comprising fixing the toner for dry development obtained by the method according to [1] above to a medium by applying heat and pressure. Regarding. Effect of the Invention
[0011] According to the method of the present invention, a toner for dry development excellent in both gloss and hot offset resistance can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The method for producing the toner for developing electrostatic images of the present invention is characterized in that it uses an amorphous polyester resin (amorphous polyester resin A) using polyethylene terephthalate (PET) and uses an open roll type twin-screw kneader for melt-kneading the raw materials. The reason why the toner for developing electrostatic images obtained by the method for producing the present invention has excellent hot offset resistance and gloss is not clear, but is presumed to be as follows.
[0013] If the elasticity of the toner is increased in consideration of hot offset resistance, the toner becomes less likely to wet and spread when fixed, resulting in a decrease in gloss. On the other hand, if the elasticity of the toner is decreased in consideration of gloss in order to improve the wet-spreadability of the toner, offset occurs at high temperatures. Therefore, in order to achieve both hot offset resistance and gloss, it is necessary to control the elasticity of the toner. When a twin-screw extruder is used to melt and knead the raw materials in the production of toner, the kneading strength is low, so that the molecular chains of the resin are not easily cut, and a large amount of highly elastic components remain, so that the toner obtained has excellent hot offset resistance but tends to have poor gloss. Conversely, when the amount of highly elastic components is reduced by lowering the molecular weight, the hot offset resistance decreases and it becomes difficult to control the physical properties. On the other hand, when an open-roll type twin-screw kneader with a strong kneading strength is used, the resin molecules are cut, resulting in low elasticity, and as a result, the toner obtained has excellent gloss but tends to have poor hot offset resistance. In the present invention, by using an amorphous polyester resin using PET as the amorphous resin, it was found that the toner obtained has excellent gloss while maintaining hot offset resistance, even when an open roll type twin screw kneader with strong kneading strength is used. In the polycondensation reaction of the alcohol component, the carboxylic acid component, and the PET, the PET is depolymerized and incorporated into the polyester resin chain by the ester exchange reaction, but it is not completely randomized, and the resulting resin contains units that can be called PET segments. As a result, it is believed that the interaction between the PET segments, which have a certain length, is strong, and therefore the molecular chain is suppressed from being cut, and even when an open roll type twin screw kneader with strong kneading strength is used, the elasticity of all the resin is not reduced, and a moderate amount of high elasticity components remain, so that the toner obtained has excellent hot offset resistance and gloss.
[0014] The amorphous polyester resin A is a polycondensation product of an alcohol component, a carboxylic acid component, and PET.
[0015] As the alcohol component, from the viewpoint of low temperature fixability, a compound represented by the formula (I):
[0016] [ka]
[0017] (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added, each of which is a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) The alkylene oxide adduct of bisphenol A represented by formula (I) is preferably a compound represented by the formula (I). Examples of the alkylene oxide adduct of bisphenol A represented by formula (I) include a polyoxypropylene adduct of 2,2-bis(4-hydroxyphenyl)propane, a polyoxyethylene adduct of 2,2-bis(4-hydroxyphenyl)propane, etc. It is preferable to use one or more of these.
[0018] The content of the alkylene oxide adduct of bisphenol A represented by formula (I) in the alcohol component is preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 100 mol %. However, the alcohol component here does not include the ethylene glycol unit of PET.
[0019] Examples of other alcohol components include aliphatic diols and trihydric or higher alcohols.
[0020] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-butenediol, 1,3-butanediol, and neopentyl glycol.
[0021] Examples of the trihydric or higher alcohol include glycerin, trimethylolpropane, and pentaerythritol.
[0022] From the viewpoint of hot offset resistance, the carboxylic acid component preferably contains an aromatic dicarboxylic acid compound.
[0023] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0024] The content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and still more preferably 95 mol% or more, and 100 mol% or less, and when the carboxylic acid component contains a trivalent or higher carboxylic acid compound, it is preferably 90 mol% or less, more preferably 85 mol% or less, provided that the carboxylic acid component does not include the terephthalic acid unit contained in PET.
[0025] Examples of other carboxylic acid components include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with a hydrocarbon group, aliphatic dicarboxylic acids such as glutaric acid, adipic acid, and sebacic acid, trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0026] In order to adjust the softening point, trivalent or higher raw monomers may be used for the alcohol component and / or carboxylic acid component of the amorphous polyester resin A. In this case, in order to improve hot offset resistance, it is preferable to use a trivalent or higher polyvalent carboxylic acid compound, preferably a trimellitic acid compound, and more preferably trimellitic anhydride. The content of the trivalent or higher raw monomer is preferably 3 mol% or more, more preferably 5 mol% or more, and preferably 30 mol% or less, more preferably 20 mol% or less, based on the total amount of the alcohol component, the carboxylic acid component, and the PET.
[0027] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.
[0028] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol component and the carboxylic acid component.
[0029] PET is produced by polycondensation of alcohol and carboxylic acid, and / or by depolymerization of a portion of PET. The ethylene glycol and terephthalic acid are used as raw monomers in the polycondensation reaction and are incorporated into polyester resin. PET is an equimolar polycondensation product of ethylene glycol and terephthalic acid, and the ethylene glycol and terephthalic acid that make up PET are regarded as the alcohol and carboxylic acid components, respectively.
[0030] The PET may be new virgin PET or recycled PET. Recycled PET is made by collecting used PET, washing it as necessary, and separating it from other materials before crushing it. The crushed material is then depolymerized to break it down into monomer units, which are then used to resynthesize the material.
[0031] In the present invention, the PET is preferably a PET having a relatively low IV value, i.e., a low molecular weight, compared to conventionally used PET. By introducing a PET having a low IV value (low molecular weight) into the polyester resin, the depolymerization of the PET proceeds more uniformly.
[0032] From the above viewpoints, the IV value of PET is preferably 0.40 or more, more preferably 0.45 or more, even more preferably 0.50 or more, and even more preferably 0.55 or more, and from the viewpoints of low-temperature fixability and uniformity of depolymerization, it is preferably 0.80 or less, more preferably 0.75 or less, even more preferably 0.70 or less, and even more preferably 0.65 or less. The IV value is an intrinsic viscosity and is an index of molecular weight. The IV value of PET can be adjusted by the polycondensation time, etc.
[0033] Commercially available PET products with an IV value of 0.40 or more and 0.85 or less include RAMAPET L1 (manufactured by Indorama Ventures, IV value: 0.60), RAMAPET BF3067 (manufactured by Indorama Ventures, IV value: 0.65), RAMAPET N2G (manufactured by Indorama Ventures, IV value: 0.75), TRN-NTJ (manufactured by Teijin Limited, IV value: 0.53), TRN-RTJC (manufactured by Teijin Limited, IV value: 0.64), RAMAPET S1 (manufactured by Indorama Ventures, IV value: 0.84), and UK-31 (manufactured by Utsumi Recycle Systems Co., Ltd., IV value: 0.67).
[0034] The content of the low IV PET in the total amount of PET used in polycondensation is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and still more preferably 100% by mass.
[0035] From the viewpoint of hot offset resistance, the PET content is preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 20 mol % or more, and is preferably 75 mol % or less, more preferably 70 mol % or less, even more preferably 60 mol % or less, of the total amount of the alcohol component, the carboxylic acid component, and the PET. When the amorphous polyester resin A is composed of two or more resins, the PET content of the amorphous polyester resin A is the weighted average value of the PET contents of the respective resins.
[0036] When the amorphous polyester resin A is composed of a resin AH and a resin AL described below, it is preferable that the resin AH has a higher PET content than the resin AL from the viewpoint of hot offset resistance.
[0037] The PET content in resin AH is, in terms of the total amount of the alcohol component, the carboxylic acid component, and the PET, preferably 4 mol % or more, more preferably 20 mol % or more, and even more preferably 40 mol % or more from the viewpoint of hot offset resistance, and preferably 80 mol % or less, more preferably 75 mol % or less, and even more preferably 65 mol % or less from the viewpoint of gloss. In addition, the content of PET in resin AL, based on the total amount of the alcohol component, the carboxylic acid component, and the PET, is preferably 4 mol % or more, more preferably 15 mol % or more, and even more preferably 25 mol % or more from the viewpoint of hot offset resistance, and is preferably 70 mol % or less, more preferably 55 mol % or less, and even more preferably 45 mol % or less from the viewpoint of gloss. In addition, since PET is a polycondensation product of ethylene glycol and terephthalic acid, dimethyl terephthalate, etc., the terephthalic acid-ethylene glycol unit (Mw: 192) is calculated as 1 mole. Therefore, the number of moles of PET = the number of moles of ethylene glycol units = the number of moles of terephthalic acid units.
[0038] The equivalent ratio (COOH group / OH group) of the carboxylic acid component (including the terephthalic acid unit in the PET) to the alcohol component (including the ethylene glycol unit in the PET) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0039] The amorphous polyester resin A can be produced, for example, by polycondensing an alcohol component, a carboxylic acid component, and PET in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and further, if necessary, in the presence of a cocatalyst, a polymerization inhibitor, etc., at a temperature of preferably 160°C or higher, more preferably 200°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.
[0040] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropoxybis(triethanolaminate) and titanium dihydroxybis(triethanolaminate). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the co-catalyst for the esterification catalyst include gallic acid. The amount of the co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0041] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.
[0042] From the viewpoints of hot offset resistance and gloss, the softening point of the amorphous polyester resin A is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, and is preferably 170°C or lower, more preferably 160°C or lower, and even more preferably 150°C or lower.
[0043] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, that is, the value of [softening point / maximum endothermic peak temperature]. An amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the resin has a crystallinity index of more than 1.4, preferably more than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. On the other hand, the crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.
[0044] From the viewpoints of low-temperature fixability and fixing width, it is preferable that the amorphous polyester resin A contains two kinds of amorphous polyester resins having different softening points. The difference in softening point between the two kinds of resins is preferably 10° C. or more, more preferably 20° C. or more, and is preferably 60° C. or less, more preferably 40° C. or less.
[0045] The softening point of the amorphous polyester resin having a higher softening point (resin AH) is, from the viewpoints of hot offset resistance and gloss, preferably 100°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, and is preferably 170°C or lower, more preferably 160°C or lower, even more preferably 150°C or lower.
[0046] Furthermore, the softening point of the amorphous polyester resin (resin AL) having a lower softening point is, from the viewpoints of hot offset resistance and gloss, preferably 70°C or higher, more preferably 90°C or higher, even more preferably 100°C or higher, and is preferably 130°C or lower, more preferably 125°C or lower, even more preferably 120°C or lower.
[0047] The mass ratio of resin AH to resin AL (resin AH / resin AL) is preferably 30 / 70 or more, more preferably 50 / 50 or more, even more preferably 55 / 45 or more, even more preferably 60 / 40 or more, and preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 75 / 25 or less.
[0048] The glass transition temperature of the amorphous polyester resin A is preferably 40° C. or higher, more preferably 50° C. or higher, and is preferably 80° C. or lower, more preferably 70° C. or lower, from the viewpoints of hot offset resistance and gloss.
[0049] From the viewpoint of hot offset resistance and gloss, the acid value of the amorphous polyester resin A is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, and is preferably 20 mgKOH / g or less, more preferably 18 mgKOH / g or less.
[0050] In the toner, the amorphous polyester resin A is contained as a binder resin.
[0051] Other examples of the binder resin include vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.
[0052] The content of the amorphous polyester resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0053] In addition, the content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably less than 100% by mass, more preferably 98% by mass or less, even more preferably 95% by mass or less.
[0054] In addition to the binder resin, additives such as colorants, release agents, charge control agents, magnetic powders, flowability improvers, conductivity regulators, reinforcing fillers such as fibrous substances, antioxidants, and cleaning improvers may be used as raw materials for the toner.
[0055] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.
[0056] From the viewpoint of improving the image density and low-temperature fixability of the toner, the amount of the colorant used is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0057] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, ethylene propylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.
[0058] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of hot offset resistance of the toner, and is preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of low-temperature fixing ability.
[0059] The amount of the release agent used, from the viewpoint of the low-temperature fixability and offset resistance of the toner and the viewpoint of dispersibility in the binder resin, is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 1.5 parts by mass or more, relative to 100 parts by mass of the binder resin, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less.
[0060] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.
[0061] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).
[0062] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.
[0063] From the viewpoint of the charging stability of the toner, the amount of the charge control agent used is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0064] In the present invention, a toner is produced by a method including a step of melting and kneading a mixture containing amorphous polyester resin A and, if necessary, additives such as a colorant, a release agent, and a charge control agent, using an open-roll type twin-screw kneader (melt-kneading step), a step of pulverizing and classifying the obtained kneaded product to obtain toner base particles (pulverizing and classifying step), and a step of mixing the obtained toner base particles with external additives (external addition step).
[0065] The mixture to be melt-kneaded may be kneaded all at once or in portions, but it is preferable to mix the mixture in advance in a mixer such as a Henschel mixer or a ball mill and then supply the mixture to an open roll type kneader.
[0066] The open-roll type twin-screw kneader refers to a kneader equipped with two rolls, in which the kneading section is open and not sealed (two-roll open-roll type kneader), and can easily dissipate the heat of kneading generated during melt kneading. The open-roll type twin-screw kneader used in the present invention is equipped with a raw material supply port and a kneaded material discharge port provided along the axial direction of the rolls, and is preferably a continuous open-roll type twin-screw kneader from the viewpoint of production efficiency.
[0067] The open-roll type twin-screw kneader used in the present invention is preferably a kneader equipped with two rolls having different circumferential speeds, i.e., a roll having a high circumferential speed (high rotation roll) and a roll having a low circumferential speed (low rotation roll). In the present invention, from the viewpoint of dispersibility of the kneaded material, it is preferable that the high rotation roll functions as a heating roll and the low rotation roll functions as a cooling roll, that is, it is preferable that the set temperature of the high rotation roll is higher than the set temperature of the low rotation roll. When the set temperatures of the rolls are different between the raw material input side and the kneaded material discharge side, it is preferable that the set temperature of the high rotation roll is higher than the set temperature of the low rotation roll at least on the raw material input side, and it is more preferable that the set temperature of the high rotation roll is higher than the set temperature of the low rotation roll on both the raw material input side and the kneaded material discharge side.
[0068] The temperature of the rolls can be adjusted, for example, by the temperature of a heat medium passed through the inside of the roll. Each roll may have its interior divided into two or more sections through which heat mediums of different temperatures are passed.
[0069] From the viewpoint of reducing the mechanical force during melt-kneading and suppressing heat generation, the temperature of the raw material input side of the high rotation roll is preferably 80° C. or higher, more preferably 100° C. or higher, and even more preferably 120° C. or higher, and is preferably 160° C. or lower, and more preferably 150° C. or lower. From the same viewpoint, the temperature of the raw material input side of the low rotation roll is preferably 25° C. or higher, more preferably 40° C. or higher, and is preferably 80° C. or lower, and more preferably 70° C. or lower.
[0070] For both the high rotation roll and the low rotation roll, it is preferable that the temperature of the raw material input side is higher than that of the kneaded material discharge side, and the temperature difference between the raw material input side and the kneaded material discharge side is preferably 20°C or more, more preferably 30°C or more, from the viewpoint of preventing the kneaded material from detaching from the rolls and from the viewpoint of reducing the mechanical force during melt kneading and suppressing heat generation, and is preferably 60°C or less, more preferably 50°C or less.
[0071] The temperatures of the raw material inlet ends of the high rotation roll and low rotation roll refer to the set temperatures of the raw material inlet ends, and the temperatures of the kneaded material discharge ends refer to the set temperatures of the kneaded material discharge ends.
[0072] The peripheral speed of the high rotation roll is preferably 2 m / min or more, more preferably 10 m / min or more, even more preferably 25 m / min or more, from the viewpoint of reducing the mechanical force during kneading and suppressing heat generation, and is preferably 100 m / min or less, more preferably 75 m / min or less, and even more preferably 50 m / min or less. From the same viewpoint, the peripheral speed of the low rotation roll is preferably 1 m / min or more, more preferably 5 m / min or more, even more preferably 15 m / min or more, and is preferably 90 m / min or less, more preferably 60 m / min or less, and even more preferably 30 m / min or less. In addition, the ratio of the peripheral speeds of the two rolls (low rotation roll / high rotation roll) is preferably 1 / 10 or more, more preferably 3 / 10 or more, and preferably 9.9 / 10 or less, more preferably 8 / 10 or less.
[0073] There are no particular limitations on the structure, size, material, etc. of each roll. The roll surface has grooves used for kneading, and the shape of these grooves may be linear, spiral, wavy, or uneven.
[0074] After the melt-kneading, it is preferable to appropriately cool the kneaded mixture until it reaches a pulverizable hardness, and then perform a pulverization and classification process to obtain toner base particles. Here, "cooling" refers to cooling the kneaded mixture to 0°C or higher and 50°C or lower, or to cooling to the glass transition temperature of the binder resin in the kneaded mixture or lower.
[0075] In pulverizing the kneaded product, the kneaded product may be pulverized to the desired particle size all at once or in stages. From the viewpoint of efficient and more uniform pulverization, however, it is preferable to perform the pulverization in two stages: coarse pulverization and fine pulverization.
[0076] Examples of the crushing machine used for the coarse crushing include a hammer mill, a cutter mill, an atomizer, and a rotoplex.
[0077] In the coarse pulverization, it is preferable to pulverize until the maximum diameter is 3 mm or less. For example, a pulverized material having a maximum diameter of 3 mm or less can be obtained by appropriately coarsely pulverizing the kneaded material until the particle size is about 0.05 mm or more and 3 mm or less, and then passing the kneaded material through a sieve with 3 mm openings.
[0078] Examples of the pulverizer used for fine pulverization include jet mills such as a fluidized bed jet mill and an impact plate jet mill, and mechanical mills.
[0079] The degree of pulverization is preferably adjusted appropriately depending on the desired particle size of the toner particles.
[0080] Examples of classifiers used for classification include airflow classifiers, inertial classifiers, sieve classifiers, etc. In the classification step, the pulverized material removed due to insufficient pulverization may be subjected to the pulverization step again, and the pulverization step and the classification step may be repeated as necessary.
[0081] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) means the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size.
[0082] Examples of the external additive used in the external addition step include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine-based resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferred, and from the viewpoint of the transferability of the toner, hydrophobic silica that has been subjected to a hydrophobic treatment is more preferred.
[0083] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.
[0084] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.
[0085] The toner base particles and the external additives can be mixed in a conventional manner using a mixer such as a Henschel mixer.
[0086] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the amount of the external additive used is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner base particles, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.
[0087] The toner obtained by the method of the present invention is used for dry development, and can be used as a toner for one-component development as it is, or as a toner for two-component development mixed with a carrier, in an image forming apparatus using a one-component development system or a two-component development system, respectively.
[0088] Furthermore, the toner obtained by the method of the present invention can achieve the effect of the present invention of achieving both glossiness and hot offset resistance by using a fixing method in which the toner is fixed to a medium by heat and pressure, which causes hot offset. EXAMPLES
[0089] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.
[0090] [PET IV value] The viscosity is calculated from the following formula: Dissolve the solution at a concentration of 4 g / L in a mixed solvent of phenol / tetrachloroethane at a mass ratio of 60 / 40, measure using an Ubbelohde viscometer, and IV=(-1+√(1+4kη)) / (2kC) (In the formula, k = 0.33, C = 0.004 g / mL, and η = (t1 / t0)-1 (t0: number of seconds for the solvent alone to fall, t1: number of seconds for the sample solution to fall).)
[0091] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.
[0092] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintain at 0°C for 1 minute. Then, measure at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature.
[0093] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.
[0094] [Acid value of resin] Measure based on the method of JIS K0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K0070:1992 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).
[0095] [Melting point of release agent] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min, the amount of heat is measured, and the maximum endothermic peak temperature is taken as the melting point.
[0096] [Volume median particle size of toner base particles (D 50 )〕 Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is required.
[0097] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.
[0098] Preparation of alkenyl succinic anhydride 1 (1) Propylene tetramer (manufactured by Nippon Oil Corporation, product name: "Light Tetramer") was used and fractionated under heating conditions of 183 to 208°C to obtain an alkylene compound (a). The obtained alkylene compound (a) had 40 peaks in gas chromatography mass spectrometry described below. The distribution of the alkylene compounds was measured according to the analysis of alkylene compound A by mass spectrometry gas chromatography in JP 2014-013384 A, and the C9H 18 :0.5% by mass, C 10 H 20 :4% by mass, C 11 H 22 :20% by mass, C 12 H 24 :66% by mass, C 13 H 26 :9% by mass, C 14 H 28 : 0.5% by mass (6 peaks corresponding to alkylene compounds having 9 to 14 carbon atoms).
[0099] (2) 542.4 g of alkylene compound (a), 157.2 g of maleic anhydride, 0.4 g of antioxidant "Chelex-O" (SC Organic Chemical Co., Ltd., Triisooctyl phosphite), and 0.1 g of butyl hydroquinone as a polymerization inhibitor were charged into a 1 L autoclave manufactured by Nitto Koatsu Co., Ltd., and pressurized nitrogen replacement (0.2 MPaG) was repeated three times. After stirring was started at 60 ° C, the temperature was raised to 230 ° C over 1 hour and the reaction was carried out for 6 hours. The pressure when the reaction temperature was reached was 0.3 MPaG. After the reaction was completed, the mixture was cooled to 80 ° C, returned to normal pressure (101.3 kPa), and transferred to a 1 L four-neck flask. The mixture was heated to 180 ° C with stirring, and the remaining alkylene compound was distilled off at 1.3 kPa for 1 hour. Subsequently, the mixture was cooled to room temperature (25° C.) and then returned to normal pressure (101.3 kPa) to obtain 406.1 g of the target product, alkenyl succinic anhydride A. The average molecular weight of alkenyl succinic anhydride A calculated from the acid value was 268.
[0100] Resin manufacturing example 1 The alcohol components, carboxylic acid components other than trimellitic anhydride, PET, esterification catalyst and cocatalyst shown in Tables 1 to 3 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, trimellitic anhydride shown in Tables 1 to 3 was added, and the mixture was reacted at 210°C for 1 hour, and then the reaction was continued at 210°C under a reduced pressure of 10 kPa until the softening points shown in Tables 1 to 3 were reached, to obtain amorphous polyester resins (resins AH1 to AH4, AH8, AH12 to AH15). The physical properties are shown in Tables 1 to 3.
[0101] Resin manufacturing example 2 The alcohol component, PET, esterification catalyst and cocatalyst shown in Table 1 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the mixture was heated to 235°C under a nitrogen atmosphere, and then polycondensed at 235°C for 6 hours. The temperature was then lowered to 210°C, and trimellitic anhydride shown in Table 1 was added, and the mixture was reacted at 210°C for 1 hour. The reaction was then continued at 210°C under a reduced pressure of 10 kPa until the softening point shown in Table 1 was reached, to obtain an amorphous polyester resin (resin AH5). The physical properties are shown in Table 1.
[0102] Resin manufacturing example 3 The alcohol component, carboxylic acid component, PET, esterification catalyst and cocatalyst shown in Tables 1, 2, 4 and 5 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the mixture was heated at 180°C for 1 hour under a nitrogen atmosphere, then heated from 180°C to 235°C at a rate of 10°C / h, and polycondensed at 235°C for 5 hours. The temperature was then lowered to 210°C, and the reaction was continued under a reduced pressure of 10 kPa until the softening points shown in Tables 1, 2, 4 and 5 were reached, to obtain amorphous polyester resins (resins AH6 to AH7, resins AL6 to AL7). The physical properties are shown in Tables 1, 2, 4 and 5.
[0103] Resin manufacturing example 4 The alcohol component, PET, esterification catalyst and cocatalyst shown in Table 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and heated to 235°C under a nitrogen atmosphere, and then polycondensed at 235°C for 6 hours. The temperature was then lowered to 180°C, and trimellitic anhydride, fumaric acid and polymerization inhibitor shown in Table 2 were added. After reacting at 180°C for 1 hour, the temperature was raised from 180°C to 210°C at 10°C / h, and polycondensed at 210°C for 1 hour. Then, the reaction was continued at 210°C under reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, and an amorphous polyester resin (resin AH9) was obtained. The physical properties are shown in Table 2.
[0104] Resin manufacturing example 5 The alcohol component, carboxylic acid component other than trimellitic anhydride, esterification catalyst and cocatalyst shown in Table 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and then polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, trimellitic anhydride shown in Table 2 was added, and the mixture was reacted at 210°C for 1 hour, and then the reaction was continued at 210°C under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain an amorphous polyester resin (resin AH10). The physical properties are shown in Table 2.
[0105] Resin manufacturing example 6 The alcohol component, carboxylic acid component other than trimellitic anhydride, esterification catalyst and cocatalyst shown in Table 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C. was passed, a stirrer and a thermocouple, and the mixture was held at 180 ° C. for 1 hour under a nitrogen atmosphere, and then heated from 180 ° C. to 230 ° C. at a rate of 10 ° C. / h, and polycondensed at 230 ° C. for 5 hours. Thereafter, the mixture was cooled to 210 ° C., and trimellitic anhydride shown in Table 2 was added, and the mixture was held at 210 ° C. for 1 hour, and then reacted under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain an amorphous polyester resin (resin AH11). The physical properties are shown in Table 2.
[0106] Resin manufacturing example 7 The alcohol component, carboxylic acid component, PET, esterification catalyst and cocatalyst shown in Tables 4 to 6 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, and the reaction was carried out under a reduced pressure of 10 kPa until the softening points shown in Tables 4 to 6 were reached, to obtain amorphous polyester resins (resins AL1 to AL5, AL8, AL12 to AL15). The physical properties are shown in Tables 4 to 6.
[0107] Resin manufacturing example 8 The alcohol component, carboxylic acid component other than fumaric acid, PET, esterification catalyst and cocatalyst shown in Table 5 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and heated to 235 ° C under a nitrogen atmosphere, and then polycondensed at 235 ° C for 6 hours. The temperature was then lowered to 180 ° C, and fumaric acid and polymerization inhibitors shown in Table 5 were added, and reacted at 180 ° C for 1 hour, and then the temperature was raised from 180 ° C to 210 ° C at 10 ° C / h, and polycondensed at 210 ° C for 1 hour. Then, the reaction was continued at 210 ° C under reduced pressure of 10 kPa until the softening point shown in Table 5 was reached, and an amorphous polyester resin (resin AL9) was obtained. The physical properties are shown in Table 5.
[0108] Resin Manufacturing Example 9 The alcohol component, carboxylic acid component, esterification catalyst and cocatalyst shown in Table 5 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, and the reaction was carried out under a reduced pressure of 10 kPa until the softening point shown in Table 5 was reached, to obtain an amorphous polyester resin (resin AL10). The physical properties are shown in Table 5.
[0109] Resin manufacturing example 10 The alcohol component, carboxylic acid component, esterification catalyst and cocatalyst shown in Table 5 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C. was passed, a stirrer and a thermocouple, and the mixture was held at 180 ° C. for 1 hour under a nitrogen atmosphere, and then heated from 180 ° C. to 230 ° C. at a rate of 10 ° C. / h, and polycondensed at 230 ° C. for 5 hours. The mixture was then cooled to 210 ° C. and reacted under a reduced pressure of 10 kPa until the softening point shown in Table 5 was reached, to obtain an amorphous polyester resin (resin AL11). The physical properties are shown in Table 5.
[0110] [Table 1]
[0111] [Table 2]
[0112] [Table 3]
[0113] [Table 4]
[0114] [Table 5]
[0115] [Table 6]
[0116] Examples 1 to 15 and Comparative Examples 2 to 3 100 parts by mass of the binder resin shown in Table 7, 5 parts by mass of a colorant "ECB-301" (manufactured by Dainichi Seikagaku Kogyo Co., Ltd., phthalocyanine blue (PB15:3)), 3 parts by mass of a release agent "Carnauba Wax C1" (manufactured by Kato Yoko Co., Ltd., melting point: 83°C), 3 parts by mass of a release agent "HNP-9" (manufactured by Nippon Seiro Co., Ltd., paraffin wax, melting point: 75°C), and 0.5 parts by mass of a charge control agent "Bontron E-304" (manufactured by Orient Chemical Industries Co., Ltd.) were mixed in a Henschel mixer.
[0117] The obtained raw material mixture was fed to a continuous open-roll type twin-screw kneader "Kneedex" (manufactured by Nippon Coke & Engineering Co., Ltd.) by a table feeder, and melt-kneaded to obtain a kneaded product. The continuous open-roll type twin-screw kneader used here had a roll outer diameter of 0.14 m and an effective roll length of 0.8 m, and the operating conditions were a rotation speed of the high rotation roll (front roll) of 75 r / min (circumferential speed 33 m / min), a rotation speed of the low rotation roll (rear roll) of 50 r / min (circumferential speed 22 m / min), and a roll gap of 0.1 mm. The heating and cooling medium temperatures in the rolls were set to 150°C on the raw material inlet side of the high rotation roll and 110°C on the kneaded material discharge side, and 65°C on the raw material inlet side of the low rotation roll and 30°C on the kneaded material discharge side. The supply speed of the raw material mixture was 10 kg / h, and the average residence time was about 5 minutes.
[0118] The kneaded product obtained was cooled to 25°C and coarsely pulverized using a pulverizer "Rotoplex" (manufactured by Hosokawa Micron Corporation). A sieve with a mesh size of 2 mm was used to obtain a coarsely pulverized product with a particle size of 2 mm or less. The coarsely pulverized product obtained was finely pulverized using a I-2 type jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) and classified using an air flow classifier to obtain a volume median particle size (D 50 ) toner base particles of 7.0 μm were obtained.
[0119] 100 parts by weight of the obtained toner base particles and 1.0 part by weight of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by weight of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives were mixed in a Henschel mixer at a rotation speed of 3000 r / min (circumferential speed of 32 m / sec) for 3 minutes to obtain a toner.
[0120] Comparative Example 1 A toner was obtained in the same manner as in Example 1, except that the raw material mixture was melt-kneaded using a twin-screw extruder "PCM-30" (manufactured by Ikegai Corporation) instead of the continuous open-roll type twin-screw kneader. The operating conditions of the twin-screw extruder were a barrel set temperature of 100°C, a shaft rotation speed of 200 r / min (circumferential speed of shaft rotation of 0.30 m / sec), and a mixture supply rate of 10 kg / h.
[0121] Test Example 1 [Toner Hot Offset Resistance] The toner was mounted on a copy machine "AR-505" (manufactured by Sharp Corporation) whose fixing unit was modified to enable fixing outside the machine, and a printout was obtained in an unfixed state (print area: 2 cm × 12 cm, adhesion amount: 0.5 mg / cm 2 ). Then, using a fixing machine (fixing speed 300 mm / sec) adjusted to a total fixing pressure of 40 kgf, the temperature of the fixing roll was raised from 120°C to 200°C in 5°C increments, and a fixing test was carried out on the unfixed printed matter at each temperature. The fixing paper used was "CopyBond SF-70NA" (Sharp Corporation, 75 g / m 2 ) was used. The resulting printed image was visually observed, and the temperature at which hot offset occurred was confirmed as hot offset resistance. The results are shown in Table 7. The higher the temperature at which hot offset occurred, the better. In the table, ">200" indicates that no hot offset occurred even at 200°C.
[0122] Test Example 2 [Glossiness of printed matter] The toner was loaded into a copier "AR-505" (product name, manufactured by Sharp Corporation), and an image was printed without fixing using J paper (product name, manufactured by Fujifilm Business Innovation Co., Ltd.) as the printing medium (printing area: 2 cm × 12 cm, adhesion amount: 0.5 mg / cm 2 The fixing machine of the copier was removed and the image was fixed on the paper at 160°C and 400 mm / sec in an external fixing machine. A piece of cardboard was placed under the image, and the gloss was measured under a light irradiation condition of 60° using a gloss meter (manufactured by Horiba Ltd., product name: "IG-330"). The results are shown in Table 7. The higher the value obtained, the higher the gloss.
[0123] [Table 7]
[0124] From the above results, it is understood that toners that achieve both hot offset resistance and glossiness can be obtained in Examples 1 to 15. Comparing Examples 10 and 11, it is understood that when amorphous polyester resins with different softening points are used, the hot offset resistance is further improved by using a larger amount of PET in the resin with a higher softening point than in the resin with a lower softening point. In contrast, Comparative Example 1, in which a twin-screw extruder was used for melt-kneading, was lacking in gloss, and Comparative Example 2, in which an amorphous polyester resin without PET was used, and Comparative Example 3, in which ethylene glycol and terephthalic acid, which are monomer components of PET, were used instead of PET, showed a particularly significant decrease in hot offset resistance. [Industrial Applicability]
[0125] The toner for dry development obtained by the method of the present invention is suitably used for dry development of latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.
Claims
1. A method for producing a toner for dry development containing an amorphous polyester resin A, the amorphous polyester resin A being a polycondensate of an alcohol component, a carboxylic acid component, and polyethylene terephthalate, the method comprising: a step of melt-kneading a mixture containing the amorphous polyester resin A using an open-roll type twin-screw kneader; a step of pulverizing and classifying the obtained kneaded product to obtain toner base particles; and a step of mixing the obtained toner base particles with an external additive.
2. 2. The method for producing a toner for dry development according to claim 1, wherein the content of polyethylene terephthalate in the amorphous polyester resin A is 5 mol % or more and 75 mol % or less of the total amount of the alcohol component, the carboxylic acid component and the polyethylene terephthalate, assuming that a terephthalic acid-ethylene glycol unit is 1 mol.
3. 3. The method for producing a toner for dry development according to claim 1, wherein the IV value of the polyethylene terephthalate is from 0.40 to 0.
80.
4. 3. The method for producing a toner for dry development according to claim 1, wherein the amorphous polyester resin A contains two kinds of amorphous polyester resins having different softening points.
5. 3. The method for producing a toner for dry development according to claim 1, wherein the open-roll type twin-screw kneader is a kneader equipped with two rolls having different peripheral speeds, the roll having a higher peripheral speed being a heating roll and the roll having a lower peripheral speed being a cooling roll.
6. 3. A method for fixing a toner, comprising fixing the toner for dry development obtained by the method according to claim 1 or 2 onto a medium by applying heat and pressure.
Citation Information
Patent Citations
Electrostatic charge image developing toner
JP2004280084A
Polyester resin for electrostatic charge image developing toner and method of manufacturing the same, electrostatic charge image developing toner and method of manufacturing the same, electrostatic charge image developer, image forming method, and image forming device
JP2009192856A
Toner composition and method for production thereof
JP2009288805A
Toner, developer, image forming method and process cartridge
JP2012194201A
Manufacturing method of toner for electrostatic charge image development
JP2014085588A